Efficacy and safety of peficitinib (ASP015K) in patients with rheumatoid arthritis and an inadequate response to methotrexate: results of a phase III randomised, double-blind, placebo-controlled trial (RAJ4) in Japan. Issue 10 (October 2019) - Takeuchi, Tsutomu; Tanaka, Yoshiya; Tanaka, Sakae; Kawakami, Atsushi; Iwasaki, Manabu; Katayama, Kou; Rokuda, Mitsuhiro; Izutsu, Hiroyuki; Ushijima, Satoshi; Kaneko, Yuichiro; Shiomi, Teruaki; Yamada, Emi; et al.
Abstract : Objective: To evaluate the efficacy and safety of the oral Janus kinase (JAK) inhibitor peficitinib versus placebo in Japanese patients with rheumatoid arthritis (RA). Methods: In this multicentre, double-blind, parallel-group, placebo-controlled phase III study, patients with RA and inadequate response to methotrexate (MTX) were randomised 1:1:1 to placebo, peficitinib 100 mg once daily or peficitinib 150 mg once daily with MTX for 52 weeks. Based on baseline randomisation, at week 12, non-responders receiving placebo were switched to peficitinib until the end of treatment; the remaining patients were switched to peficitinib at week 28. Primary efficacy variables were American College of Rheumatology (ACR)20 response rate at week 12/early termination (ET) and change from baseline in van der Heijde-modified total Sharp score (mTSS) at week 28/ET. Results: 519 patients were randomised and treated. Significantly more (p<0.001) peficitinib (58.6%, 100 mg; 64.4%, 150 mg) than placebo (21.8%) recipients achieved ACR20 response at week 12/ET. Significantly lower (p<0.001) mean changes from baseline in mTSS at week 28/ET occurred in peficitinib (1.62, 100 mg; 1.03, 150 mg) than placebo (3.37) recipients. Peficitinib was associated with haematological and biochemical parameter changes, and increased incidence of serious infections and herpes zoster-related disease. One death from suicide occurred in a patient in the placebo group after switching to peficitinib 100 mg. Conclusions: In Japanese patients with RA and inadequate response to MTX, peficitinib demonstrated significant superiority versus placebo in reducing RA symptoms and suppressing joint destruction. Peficitinib had an acceptable safety and tolerability profile, with no new safety signals compared with other JAK inhibitors. Trial registration number: NCT02305849 .